Paradojas y desafíos de las "primaveras árabes" (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The Arab Spring was the beginning of fragile political transitions, but we don’t know for sure whether they are leading towards democracy, as the young protesters of Tunis or Cairo thought, or towards the rule of Sharia as those who later took over the revolution claim. This spring splendor presented by the media was clearly overstated. We could talk of a paradox, because those movements portending changes have produced an involution after the results of the elections. Behind these active minorities, there were and still are deeply conservative and patriarchal societies, contented by the lesser evil of the status quo. We can also talk of challenges. The great challenge for the Arab world is to achieve a sustained growth capable of providing employment to all these young people. The Obama era, with his famous speech at the American University in Cairo in May 2009, normalized the relationships with moderate Islamism, hitherto demonized and which today bears the responsibility of leading those 2011 springs towards success or failure.